ANALISIS GAYA BAHASA PERBANDINGAN PADA ASPEK SIMILE DALAM NOVEL MARMUT MERAH JAMBU KARYA RADITYA DIKA - Youngky Prasetya; Erlina Zahar; Harbeng Masni (Universitas Batanghari, 2018)
This research is aimed at describing figurative language in simile aspect in the Novel Marmut Merah Jambu by Raditya Dika. This research is qualitative descriptive. The data of this research is primary and secondary data. The primary data is taken directly while secondary data is taken from books, notes, and certain evidence, or published or unpublished archives. The result of the researc identifies that there are 8 quotes of figurative language in simile aspect which is found in the novel Marmut Merah Jambu by Raditya dika.Kata Kunci: analisys, figurative language, novel